Improving the Spiritual and Educational Education of Young People the Importance of Books and Reading - Atajanova, Sharipova Dilbarxan (International Journal of Human Computing Studies, 2023)
The article discusses the importance and characteristics of books and reading in improving the spiritual and educational education of young people. Also, the factors of book and reading culture implemented in our country in educating young people to become mature individuals were discussed.